2021
DOI: 10.1103/physrevb.103.054302
|View full text |Cite
|
Sign up to set email alerts
|

Limits of the quasiharmonic approximation in MgO: Volume dependence of optical modes investigated by infrared reflectivity and ab initio calculations

Abstract: Experimental and numerical investigation of phonon optical modes of MgO as a function of temperature (from 300 to 1400 K) and pressure (from 0 to 21 GPa) are here presented. Infrared reflectivity measurements were performed to probe energies and widths of the optical phonons, as well as of the multiphonon processes affecting the spectral shape, over a variation of the unit cell volume exceeding 20%. Calculations within quasi harmonic approximation (QHA) account well for the volume dependence of the optical pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…However, more recent studies have shown a complex picture of the limit of quasiharmonic approximation (e.g. Giura et al, 2019;Calandrini et al, 2021), and a detailed discussion on the limit is out of the scope of this study.…”
Section: P -T -G Relationshipmentioning
confidence: 99%
“…However, more recent studies have shown a complex picture of the limit of quasiharmonic approximation (e.g. Giura et al, 2019;Calandrini et al, 2021), and a detailed discussion on the limit is out of the scope of this study.…”
Section: P -T -G Relationshipmentioning
confidence: 99%
“…The only physical quantity directly comparable between experimental and modeling results is the splitting of the longitudinal and transverse optical modes, i.e., the LO/TO splitting. This mode separation originates from the degeneracy elimination between the LO and TO phonons at the Brillouin-zone center [207]. In this regard, there is an overall reasonable agreement of reported measurements with predicted data (Table 3.1).…”
Section: Mgssupporting
confidence: 80%
“…The goal of this study is to model the reflectivity, which is characterized by a frequency band of high reflectivity, i.e., the reststrahlen band [207]. The top and bottom of this band are defined by the transverse (ω T O ) and longitudinal (ω LO ) optical modes, respectively.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The QHA is easy to implement and only requires 0 K calculations [14]. However, its temperature range of validity is difficult to assess and can strongly depend on the materials under consideration, since it is now well established that anharmonic effects, beyond the QHA, can be important far below the melting temperature [19][20][21].…”
Section: Introductionmentioning
confidence: 99%